2016
DOI: 10.17116/neiro201680624-35
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological characteristics, diagnostic criteria, and outcomes of surgical treatment of TSH-secreting pituitary adenomas

Abstract: The criterion for total tumor resection was a postoperative decrease in the TSH level to 0.1 mIU/L or less. Total resection was performed in 33% of patients with tumors of only the endosellar and endo-suprasellar localization. In most cases, tumors were plurihormonal and secreted TSH and GH and/or PRL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
2
0
4
Order By: Relevance
“…Mixed TSHomas secreting thyroid-stimulating hormone (TSH) and GH have various clinical manifestations, often presenting with acromegaly and/or thyrotoxicosis and with or without thyroid enlargement. Presently, many studies have reported poor efficacy and prognosis of mixed pituitary TSH/GH adenomas (3,4). In this case report, we retrospectively analyzed the clinical features of a case of pituitary adenoma secreting both GH and TSH simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed TSHomas secreting thyroid-stimulating hormone (TSH) and GH have various clinical manifestations, often presenting with acromegaly and/or thyrotoxicosis and with or without thyroid enlargement. Presently, many studies have reported poor efficacy and prognosis of mixed pituitary TSH/GH adenomas (3,4). In this case report, we retrospectively analyzed the clinical features of a case of pituitary adenoma secreting both GH and TSH simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The pituitary gland is an important endocrine organ, and the development of PA is accompanied by endocrine changes, and serum PRL, IGF-1, and GH determinations are the main basis for the diagnosis of pituitary tumors [ 24 ]. Changes in serum TSH, FT-4, and ACTH, which are indicators of pituitary function, can reflect pituitary function [ 25 ]. The results of this study confirmed that CAPTEM regimen significantly enhanced ORR, corrected endocrine disorders, and improved pituitary function in patients, which provide a basis for its application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…São medicamentos seguros e que podem ser associados a levotiroxina quando há supressão dos níveis dos hormônios tireoidianos. Em alguns casos, contudo, podem causar colelitíase e hiperglicemia, por isso é preciso que os pacientes sejam monitorados durante todo o tratamento (17,(26)(27)(28)(29) .…”
Section: Tratamentounclassified
“…Como alternativa aos AS, pode ser empregada a bromocriptina, visto que os receptores de dopamina 2 também estão presentes nos tumores. Esse medicamento, não obstante, possui resultados menos impactantes no quadro e as evidências dessa alternativa são ainda escassas (29) .…”
Section: Tratamentounclassified